ANALISIS STRATEGI BRAND EXTENSION KECAP ABC KE SAUS ABC TERHADAP SENSITIVITAS RESPON KONSUMEN (Studi Kasus Pengunjung Carrefour Plaza Medan Fair) - rogrius sinulingga; arlina nurbaity lubis (Jurnal Media Informasi Manajemen, 2013)
The aim of the research was to know and analyze to what extent the visitors’ sensitive response at Carrefour Plaza Medan Fair to brand extension from ABC soybean sauce to ABC sauce, and to know and analyze the direction of the visitors’ response at Carrefour Plaza Medan Fair on the brand extension from ABC soybean sauce to ABC sauce. This research was descriptive. It used descriptive analytic method and sensitive response method. In analyzing the level of sensitive response to brand extension, the researcher used Hierarchy of effect model which comprised of brand awareness, knowledge, liking, preference, conviction, and purchase. The data used in the research were primary and secondary data. The primary data were obtained by distributing questionnaires in which their measurement was measured by Likert scale. This research used 100 respondents as the samples which were obtained by using accidental sampling technique. The results of the research showed that consumers’ sensitive response to brand extension from ABC soybean sauce to ABC sauce was bigger than one which comprised of sensitive category. The direction of consumers’ response to brand extension from ABC soybean sauce to ABC sauce was positive. It indicated that brand extension from ABC soybean sauce to ABC sauce was able to make consumers (respondents) sensitive and to give positive response to purchase ABC sauce.   Keywords: Brand Extension, Sensitivity Response